THE CAUSE OF HIGH INTENSITY OF SEISMICITY IN UKRAINE - Chalyi, O.; Diaconescu, M.; Gurova, I.; Lisovyi, Y.; Pigylevsky, P.; Shcherbina, S.; Shevtsov, A.; Shumlianska, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In the article, the earthquake near Sumy is considered in detail. According to the authors, this earthquake occurred under the influence of several stress regimes. At the regional level: it is related to the transfer of stresses from the Vrancea zone along the mantle lineament of Sollogub; a change in the local stress field, which is created by blocks with different thicknesses of the earth's crust, with the presence of subcrustal thermal anomalies. The area of the location of the earthquake focus near the town of Sumy in tectonic terms is on the southwestern slope of the Voronezh crystalline massif near the northeastern side of the Dnieper-Donets Basin (DDB). The epicenter is confined to the northern extension of the Krivyy-Rig-Kremenchug suture zone. The earthquake focus is confined to the tectonic node formed by the eastern edge fault of the Krivyy-Rig-Kremenchug suture zone and the northern side fracture of the DDB. The main deep faults near the source of the earthquake are the northern side fault of the DDB rift and the northern extension of the Krivyy Rig-Kremenchug fault. The hypocenter of the event is in the area with sharp change in the structural plan of the Moho surface accompanied by a negative mantle gravitational anomaly. In the relief of the Moho surface, a superimposition of the structural plan of the northwestern direction, connected with the Devonian rift of the DDV, on the ancient structural plan of the Ukrainian shield and Voronezh crystalline massive is clearly visible. Within the DDV, the isohypses of the Moho surface clearly delineate the ascent to ~ 35 km in the central part of the rift. The Krivyy-Rig-Kremenchug suture zone is expressed in the Moho surface by a narrow elongated depression with depths of more than 50 km in the central part. Here, in the lower part of the cortex, the development of the crust-mantle mixture is observed. The Krivyy-RigKremenchug suture zone is also distinguished by the development of high-intensity deep magnetic inhomogeneities along it. In addition, here in the lower part of the crust and in the upper mantle a linear object of high electrical conductivity is isolated. Thus, the earth's crust of the region has a pronounced physic-geological heterogeneity, which creates instability of lithostatic stress, and this, in turn, is a prerequisite for the appearance of additional stresses.
Keywords: deep fault; mantle fault; magnitude; earthquake; intensity; Vrancea